The Cambridge encyclopedia of the English language - Crystal, David 1941- (Cambridge [England] Cambridge University Press, 1995)
An exploration of the history, structure, and use of the English language discusses its origins and evolution, its use in literature, and its structural features, and addresses grammar, pronunciation, and vocabulary
1. Modelling English -- pt. I. The history of English -- 2. The origins of English -- 3. Old English -- Early borrowings -- Runes -- The Old English corpus -- Literary texts -- The Anglo-Saxon chronicle -- Spelling -- Sounds -- Grammar -- Vocabulary -- Late borrowings -- Dialects -- 4. Middle English -- French and English -- The transition from Old English -- The Middle English corpus -- Literary texts -- Chaucer -- Spelling -- Sounds -- Grammar -- Vocabulary -- Latin borrowings -- Dialects -- Middle Scots -- The origins of standard English -- 5. Early modern English -- Caxton -- Transitional texts -- Renaissance English -- The inkhorn controversy -- Shakespeare -- The King James bible -- Spelling and regularization -- Punctuation -- Sounds -- Grammar -- Vocabulary -- The academy debate -- Johnson -- 6. Modern English -- Transition -- Grammatical trends -- Prescriptivism -- American English -- Breaking the rules -- Variety awareness -- Scientific language -- Literary voices -- Dickens -- Recent trends -- 7. World English -- The new world -- American dialects -- Canada -- Black English vernacular -- Australia -- New Zealand -- South Africa -- South Asia -- West Africa -- East Africa -- South-Est Asia and the South Pacific -- A world language -- Numbers of speakers -- Standard English -- The future of English -- English threatened and as threat -- pt. II. English vocabulary -- 8. The nature of the lexicon -- Lexemes -- The size of the English lexicon -- Abbreviations -- Proper names -- The size of a person's lexicon -- 9. The sources of the lexicon -- Native vocabulary -- Foreign borrowings -- Word-formation -- Unusual structures -- Lexical creation -- Literary neologism -- 10. Etymology -- Lexical history -- Semantic change -- Folk etymology -- Place names -- Surnames -- First names -- Nicknames -- Object names -- Eponyms -- 11. The structure of the lexicon -- Semantic structure -- Semantic fields -- Dictionary and thesaurus -- Collocations -- Lexical predictability -- Idioms -- Synonyms -- Antonyms -- Hyponyms -- Incompatibility -- Other sense relations -- 12. Lexical dimensions -- Loaded vocabulary -- Taboo -- Swearing -- Jargon -- Doublespeak -- Political correctness -- Catch phrases -- Vogue words -- Slogans -- Graffiti -- Slang -- Quotations -- Proverbs -- Archaisms -- Clichés -- Last words -- pt. III. English grammar -- 13. Grammatical mythology -- The nature of grammar -- Knowing vs knowing about -- Traditional grammar -- Prescriptive grammar -- The 20th-century legacy -- The main branches of grammar -- 14. The structure of words -- Morphology -- Suffixation -- Adjectives -- Nouns -- The apostrophe -- Pronouns -- Verbs -- 15. Word classes -- Parts of speech -- Traditional definitions -- New classes -- Nouns --Pronouns -- Adjectives -- Adverbs -- Verbs -- Prepositions -- Conjunctions -- Interjections -- 16. The structure of sentences -- Spoken and written syntax -- Types of sentence -- Sentence structure -- Sentence functions -- Clause elements and types -- Phrases-- Noun phrases -- Verb phrases -- Multiple sentences -- Abbreviation -- Disjuncts and comment clauses -- Reporting speech -- Sentence information -- Beyond the sentence -- pt. IV. Spoken and written English -- 17. The sound system -- Phonetics and phonology -- Vocal organs -- Vowels -- Consonants -- Syllables -- Connected speech -- Prosody -- Sound symbolism -- Pronunciation in practice -- 18. The writing system -- Graphetics and graphology -- Typography -- The alphabet -- Properties of letters -- Letter frequency -- Letter distribution -- Letter symbolism -- Analysing handwriting -- Graphetic variety -- Spelling -- Sources of irregularity -- Spelling reform -- Punctuation -- The development of the writing system pt. V. Using English -- 19. Varieties of discourse -- Structure vs use -- Pragmatic issues -- The nature of discourse -- Microlinguistic studies -- Texts and varieties -- Speech vs writing -- Mixed medium -- Monologue and dialogue -- 20. Regional variation -- Accent and dialect -- International and intranational -- A day in the life of the language -- American and British English -- American dialects -- British dialects -- Scotland -- Wales -- Ireland -- Canada -- Caribbean -- Pidgins and Creoles -- Australia -- New Zealand -- South Africa -- New Englishes -- 21. Social variation -- Sociolinguistic perspective -- Received pronunciation -- Prescriptive attitudes -- Gender -- Occupation -- Religion -- Science -- Law -- Plain English -- Politics -- News media -- Journalism -- Broadcasting -- Weather forecasting -- Sports commentary -- Advertising -- Restricted varieties -- New varieties -- 22. Personal variation -- Individual differences -- Deviance -- Word games -- Rule-breaking varieties -- The edges of language -- Jokes and puns -- Comic alphabets -- Variety humour -- Literary freedom -- Phonetics and phonology -- Graphetics and graphology -- Grammar and lexicon -- Discourse and variety -- Stylometry -- pt. VI. Learning about English -- 23. Learning English as a mother tongue -- Child language acquisition -- Literacy -- Grammatical development -- Early words and sounds -- Reading and writing -- Insufficient language -- Language disability -- 24. New ways of studying English -- Technological revolution -- Corpus studies -- National and international corpora -- Dictionaries -- Innovations -- Sources and resources -- Appendices -- I. Glossary -- II. Special symbols and abbreviations -- III. References -- IV. Further reading -- V. Index of linguistic items -- VI. Index of authors and personalities -- VII. Index of topics.
Includes bibliographical references and indexes.
Keywords: English Language -- Handbooks, manuals, etc